HISTORY OF ATTEMPTS OF PHILOSOPHICAL UNDERSTANDING OF POETIC REVELATION FROM PLATO TO JOYCE - Selishcheva, D. V. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2016)
The goal of this paper is to review the concepts that seek to grasp the object of poetic understanding, and to show the history of these concepts: from the idea of divine origin of poetic inspiration – to the understanding of the «poetic inspiration» as the cause of an individual poet – to the abandonment of the «subject» and «object», implemented in the work of Martin Heidegger. The «object» itself is lost in the first two cases, but in the third case the opening of poetry as questioning occurs, that is able to grasp not only the existence that contributed to the poetic understanding, but also being in general.